2021
DOI: 10.3390/ma14164520
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing of Fiber-Reinforced Plastic Composites Using Fused Deposition Modeling: A Status Review

Abstract: Composite materials are a combination of two or more types of materials used to enhance the mechanical and structural properties of engineering products. When fibers are mixed in the polymeric matrix, the composite material is known as fiber-reinforced polymer (FRP). FRP materials are widely used in structural applications related to defense, automotive, aerospace, and sports-based industries. These materials are used in producing lightweight components with high tensile strength and rigidity. The fiber compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(40 citation statements)
references
References 83 publications
(136 reference statements)
1
37
0
2
Order By: Relevance
“…They also provide sufficient strength to the final objects, giving them versatility, too [ 43 ]. The scientific literature reports a mechanical resistance, in terms of tensile strength, between 1.5 MPa and 150 MPa [ 41 , 45 , 48 , 49 , 53 , 57 ].…”
Section: Materials For Fff Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…They also provide sufficient strength to the final objects, giving them versatility, too [ 43 ]. The scientific literature reports a mechanical resistance, in terms of tensile strength, between 1.5 MPa and 150 MPa [ 41 , 45 , 48 , 49 , 53 , 57 ].…”
Section: Materials For Fff Technologymentioning
confidence: 99%
“…Its extrusion temperature varies from 340 to 440 °C [ 45 , 51 ]; it has a tensile strength equal to 100 MPa and Flexural strength equal to 170 MPa [ 45 , 51 ]. It is used for the manufacture of aerospace components, as well as for medical support for the regeneration of human bone tissues [ 46 , 48 , 51 ] The major limit of the PEEK is the non-biodegradability. Algarni and Ghazali in 2021 have demonstrated that the Young’s modulus and the ultimate tensile strength of PEEK are mainly influenced by the infill percentage.…”
Section: Materials For Fff Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…This Special Issue contains eleven articles, including three reviews [ 3 , 4 , 5 ], one perspective article [ 6 ], and seven research articles [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ] from leading institutes in the United States, China, Australia, Germany, Sweden, the Netherlands, Slovakia, the Czech Republic, Egypt, and United Arab Emirates. These articles cover the 3D printing of diverse materials such as metallic materials [ 5 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ], composites [ 4 , 6 ], and soft materials [ 3 ].…”
Section: Contributions To This Special Issuementioning
confidence: 99%
“…Recent trends and innovations in the printing of soft materials for wearable devices, soft robotics, and tissue engineering were reviewed by Regis et al [ 3 ]. Pervaiz et al [ 4 ] reviewed the 3D printing of fiber-reinforced plastic composites using fused deposition modeling. In fiber-reinforced plastic composites, fibers are mixed in a polymeric matrix.…”
Section: Contributions To This Special Issuementioning
confidence: 99%